(untitled) (Indian Journal of Animal Production and Management, 2015)
An experiment was conducted with 40 numbers of pregnant Assam Hill does in village Tetelia under Kamrup (Metro), Assam and the 40 does were randomly divided in two groups comprising of 20 pregnant does in each group viz., G1 (Control group) where concentrate ration was not supplemented and G2 (Experimental group) in which concentrate ration was supplemented @ 200g/ head/ day from 91 days of pregnancy up to kidding (pre-partum period) and first month of lactation (post-partum period).The average initial body weight of the does during the pre-partum period under the control and experimental groups were 16.28 ± 1.05 kg and 15.84 ± 0.60 kg respectively, while the final body weight of does were 18.91 ± 1.09 kg and 18.99 ± 0.75 kg respectively. The average initial body weight of does immediately within 24 hours of kidding (post-partum) were 16.43 ± 1.03 kg and 16.21± 0.60 kg respectively in control and experimental group while the final body weight of the does were 16.89 ± 0.99 kg and 16.74 ± 0.64 kg respectively after 1 month of lactation. No significant difference was observed in body weight of the does during the pre-partum and post-partum period in between the group. The total cumulative live weight gain during the pre-partum period were 2.63 ± 0.13 kg and 3.15 ± 0.23 kg respectively in control and experimental group while during post-partum period the total cumulative live weight gain were 0.46 ± 0.27 kg and 0.53 ± 0.08 kg respectively in control and experimental group.